Processing Speed in the Aging Process: Screening Criteria for the Spanish Quick Test of Cognitive Speed. Issue 2 (October 2014) - Subirana-Mirete, Judit; Bruna, Olga; Virgili, Carles; Signo, Sara; Palma, Carolina
A Quick Test of Cognitive Speed was administered to 357 participants without cognitive impairment, aged 18 to 85 years, to explore the effects of age on processing speed variables in Spanish speakers and to provide normative data for the test adapted to this population. Results were consistent with previous findings: correlations between age and naming times were high and statistically significant. Linear regression indicated that cognitive processing speed on this test slows 2 to 4 sec. per decade, depending on the task. Normalized data were provided. The findings concur with several studies that have linked age-cognitive impairment with slowing processing speed. This study attempted to assess the importance of this relation, as information processing speed could be considered a measure of cognitive impairment in everyday clinical screening evaluations.